2017
DOI: 10.1038/s41598-017-12478-1
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant high expression of ERα36, EGFR and HER2 is associated with aggressive behaviors of papillary thyroid carcinomas

Abstract: ERα, ERβ, PR, ERα36, EGFR and HER2 mRNA and protein expression in papillary thyroid carcinoma (PTC) were examined by real time RT-PCR and immunohistochemical staining. The mRNA and protein expression of ERα and PR were gradually increased and those of ERβ were gradually decreased from normal thyroid tissues to nodular hyperplasias (P < 0.05) and to PTCs (P < 0.05). However, the mRNA and protein expression of ERα36, EGFR and HER2 were only significantly increased in PTCs when compared with those in normal thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 49 publications
2
22
1
4
Order By: Relevance
“…Incidence of ER expression in the current study was at par with other published reports, which ranged from 17-54% [1,3,5,[14][15][16][17]. ERα expression has been correlated with tumor virulence, large tumors, extrathyroidal invasion, distant metastases, and reduced DFS [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. But on the contrary, there are reports, which showed that ERα and cosecretary proteins expression are positively associated with well-differentiated tumors and inversely with disease recurrence [1,3].…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Incidence of ER expression in the current study was at par with other published reports, which ranged from 17-54% [1,3,5,[14][15][16][17]. ERα expression has been correlated with tumor virulence, large tumors, extrathyroidal invasion, distant metastases, and reduced DFS [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. But on the contrary, there are reports, which showed that ERα and cosecretary proteins expression are positively associated with well-differentiated tumors and inversely with disease recurrence [1,3].…”
Section: Discussioncontrasting
confidence: 62%
“…Incidence of ER expression in the current study was at par with other published reports, which ranged from 17-54% [1,3,5,[14][15][16][17]. ERα expression has been correlated with tumor virulence, large tumors, extrathyroidal invasion, distant metastases, and reduced DFS [4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 57%
“…Additionally, data suggest that blocking EGFR can effectively increase the antitumor activity of selumetinib in triple-negative breast cancer, which may be related to the effect of this combination on the activation of extracellular signal-regulated kinase 1/2 and AKT [ 29 ]. In PTC, EGFR was demonstrated to upregulate in about 55% of PTCs and is correlated with aggressive behaviors of PTC [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Papillary thyroid cancer (PTC) represents about 80% of malignant thyroid tumors and is three times more common in women than in men suggesting a critical role of estrogen in its occurrence and development ( 32 34 ). Dai et al, analyzed the expression levels of ERα36, in association with the epidermal growth factor receptor (EGFR) and HER2, in PTCs, nodular hyperplasias and normal thyroid tissues ( 35 ). The results obtained highlight the existence of a significant correlation between the high levels of expression of ERα36 in PTC tissues and the progression and increase of tumor metastases.…”
Section: Erα36 In Different Types Of Tumorsmentioning
confidence: 99%